Phenomenological study of theoretical movement required for mastery of the Pak Salto technique on uneven bars - Iseki, S.; Nakamura, T.; Kanaya, M.; Shintake, Y. (Japan Journal of Physical Education, Health and Sport Sciences, 2025)
In recent years, there has been a tendency for gymnasts to aim for high scores on the uneven bars by performing a series of moves between the bars and attempting release techniques of D difficulty or higher. One important technique for incorporating a series of release techniques into the performance is the Pak Salto. This is because the Pak Salto can be directly combined with other high-difficulty separation moves and inter-bar transfers, thus garnering points for the combinations. For this reason, many athletes and their instructors are now trying to master the Pak Salto. However, athletes often face many challenges in the process of learning the Pak Salto technique and find difficulty in mastering it. Consequently, the technique is not yet fully understood, and its mastery is left to trial and error in the field. Against this background, the purpose of the present study was to clarify the skills required by adept performers of the Pak Salto from the standpoint of developmental kinematics and obtain basic data on the necessary procedures. For this purpose, a phenomenological questionnaire and interviews regarding the kinematic orientation of skilled performers were conducted and the results were analyzed to clarify the necessary skills. This allowed the authors to identify skills for optimizing the height, travel distance, and amount of rotation of the somersault, which are important for this technique, as well as tips for improving stability. The results obtained are believed to provide valuable information for athletes and their instructors who wish to learn the Pak Salto, and will also serve as a basis for the development of a teaching methodology for this technique.